Cana-de-açúcar hidrolisada para vacas em lactação - Sforcini, Mariana Paula Rossi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to evaluate chemical composition, nutrient intake, in vitro digestibility, blood parameters, milk production, milk composition and partial economic evaluation of dairy cows fed diets with different proportions of sugarcane hydrolyzed with hydrated lime and corn silage. Eight Holstein cows, designed into two 4 x 4 Latin Squares with four periods of 19 days each, 14 days of adaptation and five days of data collection. The cows were fed with diets containing 100% hydrolyzed sugarcane (HS); 70% HS + 30% corn silage (CS); 50% HS + 50% CS; and 100% CS. The concentrate was supplied at the rate of 1 kg for every 2.5 kg of milk. The sugarcane used was IAC 862480 with 12 months of growth, particle size of 8 mm, hydrolyzed with 0.5% hydrated lime (≥ 95% calcium hydroxide) + 2,0 liters water + 100 kg chopped sugarcane, based on natural matter. Diets with hydrolyzed sugarcane as the only forage and diets with 70% HS + 30% CS decreased dry matter, crude protein and digestible nutrients intake. The lower in vitro neutral detergent fiber digestibility was 34.92% for the diet with 100% hydrolyzed sugarcane. Milk yield and 3.5% fat-corrected milk yield decreased linearly (P<0.05) as corn silage was being replaced hydrolyzed sugarcane in diets. The milk composition, the levels of glucose, total protein, total cholesterol and gamma-glutamyltransferase were not influenced by different proportions of hydrolyzed sugarcane in the diets (P>0.05). Diets with hydrolyzed sugarcane showed better cost-benefit. Although all proportios can be used, it’s recommended the combination of 50% of the corn silage and hydrolyzed sugarcane due to reach results closer to corn silage and reduce the cost of the kilogram of milk

Este trabalho teve como objetivo estudar as diferentes proporções de cana-de-açúcar hidrolisada e silagem de milho na alimentação de vacas leiteiras através da composição bromatológica, consumo de nutrientes, digestibilidade in vitro, parâmetros sanguíneos, produção de leite, composição do leite e avaliação econômica parcial das dietas. Foram utilizadas oito vacas da raça Holandesa, distribuídas em dois quadrados latinos 4 x 4, com quatro períodos de 19 dias cada, sendo 14 dias de adaptação e cinco dias de coleta. As vacas foram alimentadas com dietas contendo 100% de cana-de-açúcar hidrolisada (CH); 70% de CH + 30% de silagem de milho (SM); 50% CH + 50% SM; e 100% SM. O concentrado foi fornecido na proporção de 1 kg para cada 2,5 kg de leite produzido. A cana-de-açúcar utilizada foi a IAC 862480 com 12 meses de crescimento, picada no tamanho de partícula de 8 mm, hidrolisada com 0,5% de cal hidratada (95% de hidróxido de cálcio) + 2,0 litros de água + 100kg de cana-de-açúcar picada, com base na matéria natural. As dietas com cana-de-açúcar hidrolisada como único volumoso e as dietas com 70% CH + 30% SM causaram menor consumo de matéria seca, proteína bruta e de nutrientes digestíveis. A menor digestibilidade in vitro da fibra em detergente neutro foi de 34,92% para a dieta com 100% cana-de-açúcar hidrolisada. As produções de leite e as produções de leite para 3,5% de gordura (PL3,5%G) diminuíram linearmente (P<0,05) com associação das proporções de cana-de-açúcar hidrolisada à silagem de milho nas dietas. A composição do leite, os níveis de glicose, proteína total, colesterol total e gama-glutamiltransferase não foram influenciados pelas diferentes proporções de cana-de-açúcar hidrolisada nas dietas (P>0,05). As dietas com cana-de-açúcar hidrolisada apresentaram melhor custo/beneficio. Embora todas as proporções possam ser utilizadas, recomenda-se a associação de ...
Keywords: Bovino de leite - Alimentação e rações; Cal; Leite - Produção; Leite - Composição; Nutrientes; Milk - Composition